Chloroplast translational regulation uncovers nonessential photosynthesis genes as key players in plant cold acclimation. Issue 5 (16th February 2022) - Gao, Yang; Thiele, Wolfram; Saleh, Omar; Scossa, Federico; Arabi, Fayezeh; Zhang, Hongmou; Sampathkumar, Arun; Kühn, Kristina; Fernie, Alisdair; Bock, Ralph; Schöttler, Mark A; Zoschke, Reimo
Abstract: Plants evolved efficient multifaceted acclimation strategies to cope with low temperatures. Chloroplasts respond to temperature stimuli and participate in temperature sensing and acclimation. However, very little is known about the involvement of chloroplast genes and their expression in plant chilling tolerance. Here we systematically investigated cold acclimation in tobacco seedlings over 2 days of exposure to low temperatures by examining responses in chloroplast genome copy number, transcript accumulation and translation, photosynthesis, cell physiology, and metabolism. Our time-resolved genome-wide investigation of chloroplast gene expression revealed substantial cold-induced translational regulation at both the initiation and elongation levels, in the virtual absence of changes at the transcript level. These cold-triggered dynamics in chloroplast translation are widely distinct from previously described high light-induced effects. Analysis of the gene set responding significantly to the cold stimulus suggested nonessential plastid-encoded subunits of photosynthetic protein complexes as novel players in plant cold acclimation. Functional characterization of one of these cold-responsive chloroplast genes by reverse genetics demonstrated that the encoded protein, the small cytochrome b 6 f complex subunit PetL, crucially contributes to photosynthetic cold acclimation. Together, our results uncover an important, previously underappreciated role of chloroplast translational regulation in plant cold acclimation. Abstract : Cold exposure induces translational regulation of plastid-encoded genes and reveals a critical role of a small nonessential cytochrome b6f complex subunit in chilling acclimation.